Alcohol consumption in young women: Challenges and repercussions in the current context - Martin del Campo Navarro, Alicia Sarahy (2023)
The essay explores alcohol consumption in young women and the social factors influencing their behavior. Despite the gender gap in alcohol consumption decreasing, women face conflicting demands regarding their consumption and gender performance, which can have physical and social repercussions. The essay examines the health risks associated with excessive alcohol consumption and provides an overview of current research on this behavior in women across different social and cultural contexts. The importance of addressing the contradictions women face in alcohol consumption is highlighted, emphasizing the need for nursing professionals to play a crucial role in promoting women's health and well-being through education, early detection, prevention, and intervention.